Numerical study of the texture effect on deformation-induced surface roughening in titanium polycrystals. (March 2020) - Romanova, V.; Balokhonov, R.; Emelianova, E.; Pisarev, M.; Dymnich, E.
Highlights: Micromechanical CPFEM simulations for titanium polycrystals are performed. Texture effect on deformation-induced surface roughening is studied numerically. Basal texture suppresses roughness development at micro- and mesoscales. Mesoscale dimensionless roughness parameter correlates with plastic strain value. Abstract: The influence of a texture on the mesoscale deformation-induced surface roughening in titanium polycrystals is studied using direct microstructure-based simulations. Relying on the experimental data for commercial purity titanium, equiaxed grain conglomerates are generated by the method of step-by-step packing. The grain constitutive behavior is described in terms of crystal plasticity, with the grain orientations being assigned randomly or representing a basal texture. The micro- and mesoscale roughness evolution in the model polycrystals under uniaxial tension is calculated using ABAQUS/Explicit. In order to quantify mesoscale roughening, a dimensionless roughness parameter is calculated for a set of experimental and numerical roughness profiles evolving in the course of tension. The mesoscale roughness parameter is shown to grow nonlinearly with the plastic strain of the evaluated mesoscale regions. Particularly, it begins increasing rapidly in the region of neck formation well before necking becomes macroscopically evident. The basal texture is shown to significantly affect the plastic strain localization and roughness patterns. The mesoscale roughness, strongly pronounced in the untextured polycrystal, is mostly suppressed in the presence of texture. A set of in-plane shear bands are formed in the textured polycrystal at an angle of 45° to the tensile axis much like those observed experimentally.